2002
DOI: 10.1523/jneurosci.22-17-07352.2002
|View full text |Cite
|
Sign up to set email alerts
|

No Ligand Binding in the GB2 Subunit of the GABABReceptor Is Required for Activation and Allosteric Interaction between the Subunits

Abstract: The GABA(B) receptor plays important roles in the tuning of many synapses. Although pharmacological differences have been observed between various GABA(B)-mediated effects, a single GABA(B) receptor composed of two subunits (GB1 and GB2) has been identified. Although GB1 binds GABA, GB2 plays a critical role in G-protein activation. Moreover, GB2 is required for the high agonist affinity of GB1. Like any other family 3 G-protein-coupled receptors, GB1 and GB2 are composed of a Venus Flytrap module (VFTM) that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
127
0
3

Year Published

2003
2003
2012
2012

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(145 citation statements)
references
References 62 publications
(96 reference statements)
14
127
0
3
Order By: Relevance
“…Accordingly, it has been proposed that the closure of only one VFTM within such dimeric receptor would be sufficient to activate the receptor. In agreement with this possibility, we found that the agonist GABA binds exclusivelly within the GABA B1 VFTM , and indeed, we even get data that strongly support the absence of natural ligand interacting with the GABA B2 VFTM (Kniazeff et al, 2002). This is based on the absence of selective conservation of the putative binding site of the GABA B2 VFTM during evolution, in contrast to the high degree of conservation of the equivalent site in GABA B1 and mGluRs.…”
Section: One Ligand Per Dimer Appears Sufficient For Class-c Gpcr Actsupporting
confidence: 84%
See 2 more Smart Citations
“…Accordingly, it has been proposed that the closure of only one VFTM within such dimeric receptor would be sufficient to activate the receptor. In agreement with this possibility, we found that the agonist GABA binds exclusivelly within the GABA B1 VFTM , and indeed, we even get data that strongly support the absence of natural ligand interacting with the GABA B2 VFTM (Kniazeff et al, 2002). This is based on the absence of selective conservation of the putative binding site of the GABA B2 VFTM during evolution, in contrast to the high degree of conservation of the equivalent site in GABA B1 and mGluRs.…”
Section: One Ligand Per Dimer Appears Sufficient For Class-c Gpcr Actsupporting
confidence: 84%
“…In contrast to this variety of mGluRs even further increased by the existence of various isoforms generated by alternative splicing (Pin and Duvoisin, 1995;Conn and Pin, 1997;Pin et al, 2003), only two GABA B encoding genes have been identified (Marshall et al, 1999) (Fig.1). Among these only GABA B1 appears to bind GABA B ligands (Kniazeff et al, 2002), the GABA B2 protein being required for normal functioning of the GABA B1 subunit, as we will see later (Marshall et al, 1999). Only one gene encoding a Ca 2+ -sensing receptor is known (Brown and MacLeod, 2001) (Fig.1).…”
Section: Class-c Gpcrsmentioning
confidence: 99%
See 1 more Smart Citation
“…En effet, seule la sous-unité GABA B1 lie le GABA, alors que GABA B2 est nécessaire à l'activation des protéines G [5,6], indiquant un fonctionnement asymétrique d'un dimère de RCPG, décrit depuis pour d'autres RCPG hétérodimériques, mais aussi homodimériques [7]. Chacune de ces sous-unités est constituée d'un Les récepteurs couplés aux protéines G (RCPG) sont des acteurs importants de la communication cellulaire.…”
Section: à Deux Sinon Rien : L'hétérodimère Comme Entité Fonctionnellunclassified
“…L'hétérodimérisation des deux sous-unités dans le RE masque le signal de rétention sur GABA B1 et favorise ainsi l'expression de l'hétérodimère à la surface cellulaire [26,27]. Une fois le dimère exprimé à la surface, GABA B1 peut lier le ligand et GABA B2 peut transduire l'effet du ligand en couplage avec les protéines G. La sous-unité GABA B2 possédant un domaine de liaison semblable à GABA B1, mais qui est incapable de lier le ligand, peut être considérée comme un récepteur orphelin à 7TM [28] (Figure 2). Ce mécanisme d'hétérodimérisation semble être conservé au cours de l'évo-lution puisqu'une étude réalisée chez la drosophile a confirmé le caractère obligatoire de la dimérisation pour la fonctionnalité des récepteurs D-GABA B1 et D-GABA B2 [29].…”
Section: L'hétérodimérisation Des Rcpg Orphelins : Le Moyen De Commununclassified